2017
DOI: 10.1016/j.molcel.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Dependent Shuttling of TBC1D5 Controls Plasma Membrane Translocation of GLUT1 and Glucose Uptake

Abstract: Summary Autophagy traditionally sustains metabolism in stressed cells via promoting intracellular catabolism and nutrient recycling. Here, we demonstrate that in response to stresses requiring increased glycolytic demand, the core autophagy machinery also facilitates glucose uptake and glycolytic flux by promoting cell surface expression of the glucose transporter Glut1/Slc2a1. During metabolic stress, LC3+ autophagic compartments bind and sequester the RabGAP protein TBC1D5 away from its inhibitory interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 33 publications
6
136
4
Order By: Relevance
“…Studies by Dikic et al showed that TBC1d5 switches between endosomes and autophagosomes. More recently, the Debnath group extended this study and showed that this switch could modulate retromer function under different physiological conditions such that metabolic stress leads to the association TBC1d5 with autophagosomes, promoting the recycling of GLUT1 and glucose uptake.…”
Section: Tbc1d5 Regulation Of Receptor Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Dikic et al showed that TBC1d5 switches between endosomes and autophagosomes. More recently, the Debnath group extended this study and showed that this switch could modulate retromer function under different physiological conditions such that metabolic stress leads to the association TBC1d5 with autophagosomes, promoting the recycling of GLUT1 and glucose uptake.…”
Section: Tbc1d5 Regulation Of Receptor Traffickingmentioning
confidence: 99%
“…TBC1d5 also plays a role in autophagy, a process in which cellular components are selectively targeted and degraded [27][28][29][30] . Studies by Dikic et al showed that TBC1d5 switches between endosomes and autophagosomes 28,29 .…”
Section: Tbc1d5 Regulation Of Receptor Traffickingmentioning
confidence: 99%
“…Localization of GLUT1 to the cell surface is largely regulated through its endocytic traffic (5)(6)(7)(8)(9)(10)(11), controlled, in non-transformed cells, by cytokine stimulation (12,13) or energy stress (6). In cancer cells, several oncogenic lesions, including hyper activation of the EGFR/PI3K/AKT signaling pathway, induce accumulation of GLUT1 at the cell surface resulting in increased aerobic glycolysis (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Torin1 (which inhibits both mTORC1 and mTORC2 complexes) was more effective than Rapalink (which is selective for mTORC1) (Rodrik-Outmezguine et al, 2016) in shifting cells toward ETC-dep; the higher sensitivity to Torin-1 is consistent with the role of mTORC2 in enhancing Akt activity. Similarly, the effect of inhibiting autophagy can potentially be explained by the finding that autophagy facilitates glucose transport (Roy et al, 2017). Inhibitors of other metabolic pathways showed lower sensitivity, including those targeting the pentose phosphate pathway (6AN), creatinine phosphate (BU99006), or fatty acid oxidation (etomoxir, PF05175157) ( Figures 4F and S4B).…”
Section: The Balance Between Glycolysis and Protein Translation Regulmentioning
confidence: 99%